Polyamide‐montmorillonite nanocomposites as a drug delivery system: Preparation, release of 1, 3, 4‐oxa(thia)diazoles, and antimicrobial activity. Issue 23 (18th July 2014) - Salahuddin, Nehal; Elbarbary, Ahmed; Allam, Nanis G.; Hashim, Ayat F.
ABSTRACT New microbicidal polyamides were prepared by the reaction of 5‐phenyl‐1, 3, 4, ‐oxadiazole‐2‐thiol, 5‐phenyl‐1, 3, 4‐oxadiazole‐2‐amine, and 5‐(4‐chlorophenyl)−1, 3, 4‐thiadiazole‐2‐thiol with ethyl chloroformate followed by polycondensation with polyoxypropylenetriamine (Jeffamine T403). The polyamides were modified to yield amine hydrochloride. The intercalation of polyamides into montmorillonite (MMT) was achieved through an ion exchange process between sodium cations in MMT and amine hydrochloride in the polyamides. The structure of the resulting materials was characterized with elemental analysis, proton nuclear magnetic resonance, Fourier transform infrared‐spectroscopy, X‐ray diffraction, thermogravimetric analysis, and transmission electron microscope. The release behavior of 1, 3, 4‐oxa(thia)diazoles was investigated in buffered aqueous solution at different pH values (2.3, 5.8, and 7.4). A slow release was recorded from the nanocomposites whereas; the release reaches almost 90% from polyamides. The in vitro antimicrobial activity of the polyamides and nanocomposites was studied against Gram‐negative bacteria, Gram‐positive bacteria, Yeast and the filamentous fungi by well diffusion method. The polymers showed good or moderate antimicrobial activities. However, nanocomposites showed no antimicrobial effect. Furthermore, in vivo study showed that nanocomposites had good antimicrobial activity. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 41177.